Challenges Faced in Biomedical Waste Management by Waste Handlers amidst the COVID-19 Pandemic in a Tertiary Care Hospital: A Qualitative Study - Anuradha Kunal Shah; Yuvaraj B Chavan; Nived G Sudarson; Sagar K Sontakke (Indian Association of Preventive and Social Medicine, 2022)
Introduction: Coronavirus disease 2019(COVID-19) saw an overhaul in the biomedical waste management (BMWM) practices. Waste handlers were at the brunt of these changes. If the challenges pertaining to BMWM at the ground level are better understood, more effective measures to overcome them can be formulated. Objectives: 1. To identify myths and concerns regarding BMWM in the context of COVID-19 pandemic. 2. To explore the challenges faced in BMWM amidst the COVID-19 pandemic. 3.To explore opportunities and future perspectives of BMWM. Method: In-depth interviews were conducted among 17 purposively selected Class IV health care workers during August to November 2021 in a tertiary care institute in Mumbai. Data was reported using thematic analysis. Results: Three major themes - challenges and concerns faced by BMW handlers, enablers/ motivators, opportunities and future practices were generated from the transcripts. Various challenges faced by waste handlers were- difficulties in segregation and transport of BMW, exhaustion from PPE usage and fear of acquiring and spreading COVID-19 from work, stigma faced from public, and handling COVID-19 deaths. Support from family and colleagues, incentives and a positive change in public perception enabled them to work. Forming redressal committees, addressing job security concerns and timely provision of good quality equipment can improve hospital waste management measures in the future. Conclusion: It is of utmost importance to address challenges faced by waste handlers in BMWM. Onus should also be on periodic training in BMWM.